FORMS OF AGREEMENTS IN THE CIVIL CODE THAT CAUSE COLLABORATION IN THE PROCUREMENT OF GOODS AND SERVICES - Nasution, Muhammad Anggi; Sirait, Ningrum Natasya; Siregar, Mahmul (NOMOI Law Review, 2024)
The Civil Code divides the agreement into 2 parts, named agreements and unnamed agreements. These agreements are sometimes used for tenders related to the procurement of goods and services. These forms of agreements are often used by tender participants to create a pseudo-business competition. Pseudo-business competition is commonly used to win a tender. So that this research will focus on the forms of agreements that are often used in the procurement of goods and services in Indonesia through the perspective of Law Number 5 of 1999. This research is a normative juridical research using descriptive analysis. In this study, a comprehensive, systematic and in-depth picture of a situation or signs that are studied about all related matters. Named agreements and unnamed agreements have legality in Indonesian positive law, but agreements are not allowed to be made in the procurement of goods and services, because they will violate the provisions of Article 22 with the type of horizontal conspiracy that has been detailed through the Regulation of the Business Competition Supervisory Commission Number 3 of 2023 with the type of horizontal conspiracy and violates Articles 6 and 7 of Presidential Regulation No. 16 of 2018 as amended by Presidential Regulation No. 12 of 2021, so that the agreement is null and void .